Transport Properties of GdTe1.8–xAsx (x = 0, 0.04). Issue 25 (15th June 2020) - Poddig, Hagen; Hobbis, Dean; Alzahrani, Noha; Doert, Thomas; Nolas, George S.
Abstract : Phase‐pure polycrystalline samples of GdTe1.8 and GdTe1.76 As0.04 were synthesized by reacting Gd2 Te3 with elemental Te and As, employing a small amount of I2 as mineralizer. Polycrystalline specimens were densified by SPS for temperature dependent electrical and thermal properties investigations. The electrical properties indicate that arsenic doping leads to a change from n‐ to p‐type conduction, with an order‐of‐magnitude reduction in resistivity with As doping at room‐temperature as compared to GdTe1.8 . The thermal conductivity of both specimens is low, the result of the crystal structure and atypical Te bonding in this material. The results presented are intended to expand on the research into rare‐earth polychalcogenides and advance the fundamental investigation of these materials, as well as begin to evaluate their potential for thermoelectric applications. Abstract : Short text: Temperature dependent thermal and electrical transport properties on GdTe1.8 and GdTe1.76 As0.04 are investigated on densified, polycrystalline specimens. Arsenic doping leads to a change from n‐ to p‐type conduction, and a reduction in resistivity as compared with that of undoped GdTe1.8 . These materials have low thermal conductivity, the result of the crystal structure and atypical Te bonding.